Implementation of the At Tanzil Method in Islamic Education at the At Tanzil Lembah Jaya Guidance Center in Malaysia - Watik Widianingrum; Habibatul Wildain Saharu; Sigit Dwi Laksana; Farahiyah Kurnia Putri; Kholis Frendika (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
This study examines the application of the At-Tanzil Method at the At-Tanzil Lembah Jaya Guidance Center in Selangor, Malaysia, as a structured learning approach in Islamic education within the Muslim diaspora community. This study aims to describe the stages of learning using the At-Tanzil Method and analyze its contribution to the learning development of students. This study uses a qualitative approach with a case study design. Data collection was conducted over a period of one month through observation, semi-structured interviews, and documentation. The research participants consisted of two main informants, namely the Al-Qur'an teacher and the guidance center manager, as well as students in grades IV-VI who already had basic Al-Qur'an reading skills. Student learning progress was monitored through routine evaluations twice a month using oral and written tests. The results showed that the At-Tanzil Method, which was applied through six systematic stages of tahsin, contributed to improvements in fluency, accuracy, and the application of basic tajwid rules. The bi-monthly evaluations also showed an increase in consistency in learning discipline and student engagement during the learning process. In addition to technical learning achievements, the application of this method also supports an increase in learning motivation, discipline, and religious awareness among students as part of Islamic character building. Thus, the At-Tanzil Method is effective as a structured learning approach in Islamic education and has practical implications for the development of Qur'an learning models in similar educational institutions.